Structure and electrical properties of In₂Se₃Mn layered crystals - Kaminskii, V.M.; Kovalyuk, Z.D.; Zaslonkin, A.V.; Ivanov, V.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
Investigations of the crystalline structure and electrical properties of
In₂Se₃ 1 wt. %Mn and In₂Se₃ 6 wt. % Mn crystals have been carried out. We have
found formation of a substitutional solid solution for In₂Se₃ 1 wt. %Mn single crystals as
well as existence of two phases (In₂Se₃ and MnIn₂Se₄) in polycrystalline ingots
In₂Se₃ 6 wt. % Mn. Temperature dependences of the conductivities across (σ⊥C) and along
(σ||C) the crystallographic c axis were measured in the range of 80 to 400 K. From the
anisotropy σ⊥C/σ||C of conductivity temperature dependences of the energy barrier value
ΔЕδ between the layers were calculated for the crystals under investigations.